Binge-Like, Naloxone-Sensitive, Voluntary Ethanol Intake at Adolescence Is Greater Than at Adulthood, but Does Not Exacerbate Subsequent Two-Bottle Choice Drinking - Salguero, Agustín; Suarez, Andrea; Luque, Maribel; Ruiz-Leyva, L.; Cendán, Cruz Miguel; Morón, Ignacio; Pautassi, Ricardo Marcos (Frontiers in Behavioral Neuroscience, 2020)
The present study assessed the effects of ethanol exposure during adolescence (PDs 30-56) or young adulthood (PDs 70-96). We exposed adolescent or adult, male or female, Wistar rats to self-administered 8-10% (v/v) ethanol during the first two hours of the dark cycle, three times a week for 4 weeks (BINGE group). Controls were only handled, and a third (I.P.) condition was given ethanol intraperitoneal administrations at doses that matched those self-administered by the BINGE group. The rats were tested for ethanol intake and preference in a two-bottle (24 h long) choice test, shortly before and shortly after exposure to the binge protocol; and then tested for freechoice drinking during late adulthood (PDs 120-134) in intermittent two-bottle intake tests. Binge drinking was significantly greater in adolescents vs. adults (2.5-3.0 vs 1.25 g/kg, approximately), in males vs. females, and was blocked by naloxone (5.0 mg/kg) administered immediately before the binge session. Mean blood ethanol levels (mg/dl) at termination of binge session 3 were 60.82±22.39. Ethanol exposure at adolescence, but not at adulthood, significantly reduced exploration of an open field-like chamber, increased object exploration in the novel object recognition task and significantly increased shelter-seeking behavior in the multivariate concentric square field. The rats that had been initially exposed to ethanol at adolescence drank, during the intake tests conducted at adulthood, significantly more than those that had their first experience with ethanol at adulthood, an effect that was similar among BINGE, I.P. and control groups.The study indicates that binge-like ethanol drinking is substantially greater in adolescent that in adults, is associated with an anxiety-prone phenotype and with heightened ethanol intake at adulthood. The results indicate that preventing alcohol access to adolescents should reduce the likelihood of problematic alcohol use or alcohol-related consequences.